Putting early algebra in the hands of elementary school teachers: examining fidelity of implementation and its relation to student performance / El álgebra temprana en manos del docente de primaria: un análisis de la fidelidad de ejecución y su relación con el rendimiento de los escolares. Issue 3 (3rd July 2019) - Stylianou, Despina A.; Stroud, Rena; Cassidy, Michael; Knuth, Eric; Stephens, Ana; Gardiner, Angela; Demers, Lindsay
Abstract: Guided by a theoretical framework emphasizing the importance of fidelity of implementation (FOI), this paper explores how teachers of grades 3, 4 and 5 implemented an early algebra intervention, and the relationship between FOI and student learning. The data shared in this paper come from a longitudinal experimental research project in which 3, 208 students from 46 schools were followed for three years. Videotaped classroom observations, our primary source of FOI data, were coded to capture teachers' instructional practices, and an algebra assessment was given to assess student performance in response to the teachers' implementation of our instructional intervention. Results revealed a significant positive relationship between aspects of teachers' implementation and their students' performance.